Dynamics of Local Democracy as a Context for Civic Learning: A Literature Review - Dani Ramdan (Civiliza Publishing, Indonesia., 2025)
Direct regional elections (Pilkada langsung) have become a central mechanism of local democratization in Indonesia, aiming to enhance the political legitimacy and accountability of regional leaders. However, the extent to which direct elections contribute to accountable local leadership remains debated in the literature on local politics and governance. This article aims to examine the impact of direct regional elections on the quality of local leadership, with particular attention to political and governance accountability, through a literature-based analysis. This research method employs a qualitative approach using a semi-systematic narrative literature review of scholarly works discussing direct regional elections, local democracy, leadership, and accountability in Indonesia. The selected literature is analyzed thematically to identify dominant patterns, supporting factors, and structural constraints that shape leadership accountability in the post-election context. The research findings suggest that while direct regional elections enhance electoral legitimacy, they do not automatically translate into more accountable leadership. High political costs, entrenched patronage networks, and weak oversight institutions often weaken accountability mechanisms at the local level. These dynamics are highly relevant to understanding leadership challenges in a politically and economically complex region like Bekasi Regency. This article concludes that improving the quality of local leadership requires a broader institutional and political reform agenda beyond election procedures, emphasizing stronger accountability mechanisms, democratic oversight, and meaningful citizen participation in local governance.